1998
DOI: 10.1002/clc.4960210405
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of predischarge radionuclide ventriculography at rest and exercise after acute myocardial infarction treated with thrombolytic therapy or primary coronary angioplasty

Abstract: SummaryBuckground: Previous studies have demonstrated the prognostic value of radionuclide ventriculography at rest and exercise in patients post myocardial infarction (MI). The number of studies in patients treated with modem reperfusion techniques, including thrombolysis or primary angioplasty, however, is limited.H.yporhesis: The aim of this study was to evaluate the prognostic significance of predischarge radionuclide ventriculography at rest and exercise in patients with acute MI treated with thrombolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 40 publications
0
7
0
3
Order By: Relevance
“…This is because a stress response is accompanied by high levels of catecholamines and cortisol, and these hormones increase glycogenolysis and lipolysis and reduce insulin sensitivity, resulting in elevated glucose levels (14). Therefore, patients with elevated glucose levels may represent patients with an increased stress response, for example, due to more severe hemodynamic compromise or more extensive myocardial damage (15,16). Stress hyperglycemia increases mortality, congestive heart failure and cardiogenic shock after AMI (17).…”
Section: Discussionmentioning
confidence: 99%
“…This is because a stress response is accompanied by high levels of catecholamines and cortisol, and these hormones increase glycogenolysis and lipolysis and reduce insulin sensitivity, resulting in elevated glucose levels (14). Therefore, patients with elevated glucose levels may represent patients with an increased stress response, for example, due to more severe hemodynamic compromise or more extensive myocardial damage (15,16). Stress hyperglycemia increases mortality, congestive heart failure and cardiogenic shock after AMI (17).…”
Section: Discussionmentioning
confidence: 99%
“…If this compensatory mechanism fails, left ventricular dysfunction first manifests during exercise. However, conflicting results exist on the superior prognostic value of exercise MUGA, compared with MUGA at rest (51,52). Furthermore, because certain cancers and coronary heart disease have age and smoking as 2 common major risk factors, many of these patients undergo gated myocardial perfusion SPECT to rule out ischemic heart disease.…”
Section: Noninvasive Imaging Of Cardiotoxicitymentioning
confidence: 99%
“…A meta-analysis showed that if the predischarge TET is normal following an acute MI, there is a < 10% event rate at 1 year; if abnormal, the event rate increased to 10-20% [38]. However, another study using TET in conjunction with nuclear imaging showed that neither angina pectoris nor ST-segment depression during the stress test was independently predictive for cardiac death [39]. In fact, the most powerful predictor of subsequent cardiac mortality was a lower ejection fraction at rest.…”
Section: Exercise Electrocardiography After An Acute Coronary Eventmentioning
confidence: 93%